Challenges and Opportunities of Look East Policy: A Special Reference to North East India - Dr. Rumia Begum (International Journal of Advanced Science and Technology, 2020)
The Look East policy (LEP) has emerged as an important foreign policy initiative of India in the post-Cold War period. The end of cold war brought about a fundamental change in the international system, which focuses on the economic content of relations and led to the burgeoning of the formation of regional economic organizations (Haokip 2011). LEP/AEP has evolved in four different waves over centuries and what is identified as India’s LEP since the early 1990s constitutes the fourth wave of India’s eastward (re)engagement (Muni 2013).  This paper is an attempt to understand the role of Look East Policy as a development strategy for North East India.  Firstly, the paper has focused on the objectives of LEP as well as its importance related to North East India.  The paper has also looked into the opportunities, prospects of LEP/AEP as well as the constraints faced by North East to fulfill the initiatives under LEP.